Transcription and Post-translational Regulation of Autophagy in Insects - Li, Rongsong; Xiao, Yang; Li, Kang; Tian, Ling (Frontiers in Physiology, 2022)
Autophagy attracts great attention, and numerous progresses have been obtained in the last two decades. Autophagy is implicated in mammalian neurodegenerative diseases, tumorigenesis as well as development in insects. The regulatory mechanism of autophagy is well documented in yeast and mammals, whereas, it is not fully illustrated in insects. Drosophila melanogaster and Bombyx mori are the two well-studied insects for autophagy, and several insect-mammalian evolutionarily conserved or insect-specific mechanisms in regulating autophagy are reported. In this review, we summarize the most recent studies of autophagy at both transcriptional and post-translational levels by insect hormone in cooperation with other signals such as nutrient, which will provide a reference and deep thinking for researches on autophagy in insects.